Asymmetric Dehydrative Allylation Using Soft Ruthenium and Hard Brønsted Acid Combined Catalyst. Issue 6 (21st June 2021) - Tanaka, Shinji; Kitamura, Masato
Abstract: Asymmetric Pd‐catalyzed Tsuji‐Trost‐type allylation is an important catalytic reaction toward chiral natural and unnatural product syntheses. We successfully modified a desalt‐type reaction using allyl ester or halide to a dehydrative one using allylic alcohol via the establishment of two redox‐mediated donor acceptor bifunctional catalyst systems. These systems were cationic CpRu‐Cl‐Napy‐PyCOOH and cationic CpRu‐Naph‐diPIM‐dioxo‐ i Pr/ p ‐TsOH and were designed on the basis of the soft ruthenium and hard Brønsted acid combined catalyst concept. The complementary use of the two chiral catalysts for dehydrative asymmetric allylation expands the application scope facilitating the utilization of both aliphatic and aromatic allylic alcohols with various nucleophiles in the substrate. In this account, the design, synthesis, and application of these catalysts were reported. Abstract : Two RDACat catalysts, CpRu‐2‐pyridinecarboxylic acid and CpRu‐bisamidine/ p ‐TsOH, catalyze the dehydrative allylation of various types of nucleophiles including carbon, nitrogen, and oxygen with allylic alcohol. Complementary use of these catalysts constructs the expanded range of chiral allylic compounds.